Pengembangan Sistem Informasi Data Pasien Seksi Rehabilitasi BNN Kota Malang Menggunakan Metode Iterative Incremental - Stefanus Eka Prastya; Mochamad Chandra Saputra; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Narcotics National Agency (BNN Kota Malang) is government vertical agencies whose have role in prevention, eradication of Illicit Drug Abuse is doing their job under the responsibility of the local Government of Malang City. the Rehabilitation Section's duty is recovering drug users, Rehabilitation Section storing data using paper forms. The problem is that a growing number of patient data, which stored with the conventional ways so the data search becomes longer and reduce the productivity of the employees so that the maintenance of the data becomes more complex and increase the risk of losing the physical data Information systems proven can reduce the time thus increasing productivity and effectiveness. The success of information system development depends on proper development method, the stakeholder's needs are unclear yet and the system should be able to adapt to the needs of the organization while developed are the reason we use a strategy of Incremental Iteration. This research will report the implementation of the strategy as well as other important roles, among others is the proper requirements analysis, design and the appropriate testing methods which can be measured with the real problems which result 10 functional requirements and 2 nonfunctional requirements in requirement analysis, 10 class (analysis), 9 table, 4 model, and 6 controller in design phase, 3 test case succeed in testing phase.